2013
DOI: 10.3171/2013.1.spine12628
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous treatment of subarachnoid-pleural fistula with Onyx

Abstract: Subarachnoid-pleural fistula is a well-described complication after anterior surgery for thoracic disc herniation, but is difficult to treat by means of traditional chest and lumbar drains due to interference by positive ventilation pressures that may keep the fistula open and prevent proper closure. Current treatment strategies include surgical repair, which is technically challenging, and noninvasive positive pressure ventilation, which can take several weeks to be effective. In this report, the authors desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Interventions include primary repair or use of cadaveric graft, muscle flaps, or omental flaps [2,4,6,10,11]. The repair can be augmented with a secondary layer of sealants such as fibrin glue, epidural blood patch, Tisseel, DuraSeal (Integra Lifesciences, Plainsboro, NJ), or Onyx (Medtronic-Covidien, Minneapolis, MN) [1,6,8,12]. Alternatively, noninvasive positive pressure mask ventilation combined with chest tube drainage can be used to increase intrathoracic pressure, which decreases CSF flow by decreasing the pressure gradient between the subarachnoid and pleural spaces [5,13].…”
Section: Discussionmentioning
confidence: 99%
“…Interventions include primary repair or use of cadaveric graft, muscle flaps, or omental flaps [2,4,6,10,11]. The repair can be augmented with a secondary layer of sealants such as fibrin glue, epidural blood patch, Tisseel, DuraSeal (Integra Lifesciences, Plainsboro, NJ), or Onyx (Medtronic-Covidien, Minneapolis, MN) [1,6,8,12]. Alternatively, noninvasive positive pressure mask ventilation combined with chest tube drainage can be used to increase intrathoracic pressure, which decreases CSF flow by decreasing the pressure gradient between the subarachnoid and pleural spaces [5,13].…”
Section: Discussionmentioning
confidence: 99%
“…10,20 This surgical intervention most commonly requires the use of a dural substitute or sealant (Tisseel, DuraSeal) and can be augmented with a vascularized graft. 7,8,19 Other authors have reported success with secondary occlusion of fistulas by using an epidural blood patch (EBP) 1 or synthetic material such as DuraSeal, Tisseel, and even Onyx; 4,6,11 however, all of these successes occurred in adult patients. Kurata et al reported that 5-14 days of continuous noninvasive positive pressure ventilation (NIPPV) can be used as an adjunct to chest tube drainage, with the goal of increasing intrathoracic pressure and reducing the pressure gradient between the pleural and subarachnoid spaces.…”
Section: Discussionmentioning
confidence: 99%
“…Treatments for PSF include surgery and non-surgery. Although surgical treatment is a little more common than non-surgery strategy, there are more kinds of conservative measurements including thorax drainage, lumbar cisterna drainage, keeping supine position [ 10 ], epidural blood patch [ 12 , 14 ], positive pressure ventilation [ 15 18 ], biological glue injection percutaneously [ 19 , 20 ], and so on. Percutaneous injection of biological glue was newly reported treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Complications related to the treating measure were seldom reported before. Knafo et al [ 20 ] reported the thorax pain after injection of onyx. Infection [ 22 ] and neurological defects [ 4 ] were reported separately by Wilson and Jumer and Brown and Symbas.…”
Section: Discussionmentioning
confidence: 99%